Rhizosphere‐Scale Quantification of Hydraulic and Mechanical Properties of Soil Impacted by Root and Seed Exudates - Naveed, M. (2020)
The water sorptivity and repellency index of air‐dry soil were measured using a miniaturized infiltrometer device with a 1‐mm tip radius. Soil hardness increased by 28% for barley root exudate, 62% for maize root exudate, and 86% for chia seed exudate at 4.6 mg g−1 concentration in the sandy loam soil. For the clay loam soil, root exudates did not affect soil hardness, whereas chia seed exudate increased soil hardness by 48% at 4.6 mg g−1 concentration. Soil water repellency increased by 48% for chia seed exudate and 23% for maize root exudate but not for barley root exudate at 4.6 mg g−1 concentration in the sandy loam soil. For the clay loam soil, chia seed exudate increased water repellency by 45%, whereas root exudates did not affect water repellency at 4.6 mg g−1 concentration. Water sorptivity and repellency were both correlated with hardness, presumably due to the combined influence of exudates on the hydrological and mechanical properties of the soils.